(untitled) (Itinera, 2012)
S. Langer captures the possibility of comprehension beyond symbolical logic and identifies symbols capable of expressing the richness of human experience. Art interprets our interior life and explores the image of external reality which we have developed thanks to rhythmic forms and “feeling”. Langer explores what she defines as “symbol”, “language”, “limits of language”, “vitality” and “expression” to clarify the nature of art and her approach to emotions.